Stress Transformation Calculations - Rossow, Mark (McGraw-Hill's AccessEngineering., 2017)
In a body in a state of plane stress, the normal and shear stresses acting on a plane at a point in the body are governed by the equations of stress transformation. This Excel workbook employs these equations to calculate the principal stresses, principal angle, and maximum in-plane shear stress. The workbook also calculates the stresses acting on a plane inclined at an angle (specified by the user) with respect to the coordinate axes.